Augmented reslity application builder:integration of finger tracking for interaction in augmented reality system - Choong, Allen Chieng Hoon. (Universiti Malaysia Sarawak, (UNIMAS), 2010)
Augmented Reality (AR) is a technology that generates virtual information to the real world to the users perception and interaction to perform the tasks. This research studied adn developed a computer library, AR Application builder, which was integrated with the finger tracking feature for the interaction with the virtual objects in the AR system. The AR Application Builder allows user to build AR applications. Hence, the users are able to use their bare finger to interact with the virtual objects. The development of the AR Application Builder involved video capturing, image processing, vision-based AR registration, virtual objects generation and finger tracking.